The Method of Bank Efficiency Analysis: Cost and Profit Function - Jerry Marmen Simanjuntak (International Journal of Economics Development Research (IJEDR), 2024)
Understanding the factors influencing bank efficiency is crucial for maintaining the health of financial institutions and fostering broader economic growth. From a strategic management perspective, suboptimal bank performance often stems from specific internal and external factors, such as inefficiencies in resource management, organizational development, and competitive strategy implementation. Over the past two decades, scholars, practitioners, and policymakers have increasingly focused on analyzing the complexities of bank performance. This study employs a qualitative descriptive approach to provide a comprehensive analysis of bank efficiency, focusing on cost and profit functions. The cost function examines the relationship between input prices and output levels, illustrating that costs vary with changes in output quantity and input prices. Conversely, the profit function assesses how profits are influenced by variations in both input and output prices, offering a more nuanced understanding of how banks can optimize their financial performance. By integrating these two critical functions, the research makes significant contributions to the literature on bank efficiency, providing practical insights for bank management and regulators. It underscores the importance of closely monitoring and optimizing cost and profit functions to ensure sustained efficiency within the banking sector. Additionally, the study advances theoretical understanding by bridging traditional economic models with modern strategic management theories, offering a more holistic view of bank efficiency. The research also suggests avenues for future studies to explore the interplay between cost and profit functions across various banking environments, thereby enhancing both the theoretical and practical knowledge of bank performance.